EQUITY EDUCATION IN THE MULTICULTURAL CONTEXT: A SYSTEMATIC LITERATURE REVIEW OF STUDIES (2013-2022) - Puteri, Celiacika Gustisiwi (International Journal of Education, 2025)
Although the provision of egalitarian education in a multicultural context is deemed fundamental, this field has not received considerable concern. Using a systematic literature review and meta-analysis, this study aims to review 44 articles on multicultural context equity education from the Scopus database between 2013 and 2022, which include the following five research problems: (1) the number of publications and the geographical distribution; (2) authors making the most significant contributions; (3) articles having the greatest influence on the field of equity education in multicultural settings; (4) research methodology; and (5) perceptions and attitudes toward equity education in multicultural context. The findings reveal that the United States is the predominant source of all publications. While the most significant articles are from the United States, one of the most prolific authors is from China. Almost all of publications employ qualitative research method and are descriptively analyzed. Observations, interviews, document analysis, and questionnaires are frequently applied instruments. To mitigate this predominance, prospective research might adopt mixed-method approaches that integrate the profundity of qualitative analysis with the generalizability inherent in quantitative studies. Scholars believe that the issue of the number of minority groups who face challenges to engage in the education sector must be addressed. Therefore, policies that ensure diverse communities receive an equitable education are essential.